Green cockpit: Transparency on energy consumption in manufacturing companies - Rackow, Tobias; Javied, Tallal; Donhauser, Toni; Martin, Andreas; Schuderer, Peter; Franke, Jörg (12th Global Conference on Sustainable Manufacturing, GCSM 2014, 2015)
Companies are forced by rising energy costs to seize control of their energy consumption to maintain contestability. Therefore, transparency over the companies' energy flux along the production process is required. Energy data management software is helpful, but cost-intensive. Hence, especially small and medium sized enterprises (SME) spare this investment. In this paper, the requirements for an energy controlling infrastructure in SME are elaborated, followed by a deduced software-architecture which supports the respective controlling structure. Further, the prototypical realization of the corresponding tool "Green-Cockpit" will be presented. The free of cost, open source and web-based tool is designed to help companies monitor, interpret, analyze, plan and report their energy consumption. The Green Cockpit tool outperforms other energy management software at management disciplines with its ability to not only analyze energy consumption, but plan and control it additionally.
Keywords: Energy controlling; Energy management; Open source data management; Operations management